Designing Student’s Registration Book and Student’s Report Card Processing Application For Pangudi Luhur Don Bosko Elementary School Semarang - Adrianus Hermawan Susanto; Erdhi Widyarto; Bernardinus Harnadi (SISFORMA, 2020)
The development of information and communication technology continues to run over time in various fields, without exception in the field of education. Master data management of students has now started using electronic media. At Pangudi Luhur Don Bosko Elementary School also used electronic media in its management, but the application has limitations in storing data, therefore the authors designed the "Student’s Registration Book and Student’s Report Card Processing Application for Pangudi Luhur Don Bosko Elementary School". The purpose of this research is to design and build student’s registration book and student’s report card processing so that it can facilitate data processing, and determine the factors that influence users to adopt this application. This writing method starts with a literature study followed by the design and construction of the application, the next step is testing the application to making report card. This application is able to store data with a much larger capacity, so it can continue to be used for years. This application can process student data and be a good student data archive. The factor that can influence the user to adopt this application is the student report card archiving feature with a very complex K13 model.